Multidisciplinary Postoperative Care Pathway to Reduce Readmissions following Endoscopic Transsphenoidal Pituitary Surgery: Improving Quality of Patient Care - Ghiam, Michael K.; Ali, Ibrahim A.; Dable, Cortney L.; Ayala, Alejandro R.; Kargi, Atil Y.; Komotar, Ricardo J.; Levine, Corinna G.; Sargi, Zoukaa (Journal of Neurological Surgery Part B: Skull Base, 2022)
Background Thirty-day unplanned readmission following endoscopic transsphenoidal pituitary surgery (ETPS) occurs in up to 14% of patients. Delayed hyponatremia is one of the most common causes, accounting for 30% of readmissions and often occurs within 1 week of surgery. The authors' prior retrospective review identified endocrinology follow-up as protective factor.Objectives Implementation of a multidisciplinary postoperative care (POC) pathway: (1) to reduce 30-day hospital readmissions following ETPS and (2) improve inpatient and outpatient coordination of care with endocrinologist.Methods This study is a single institution temporal cohort study of patients prior to (control cohort) and after implementation of the POC pathway (intervention cohort). The POC pathway utilized postdischarge 1 to 1.5 L/d fluid restriction, postoperative days 5 to 7 serum sodium, and endocrinology follow-up within 1 week of discharge to stratify patients into tiered hyponatremia regimens.Results A total of 542 patients were included in the study, 409 (75%) in the control cohort and 133 (25%) in the intervention cohort. All-cause readmission was significantly reduced following implementation of the POC pathway (14 vs. 6%, p = 0.015). Coordination with endocrinologist significantly increased in the inpatient (96 vs. 83%, p < 0.001) and outpatient (77 vs. 68%, p = 0.042) settings. Patients who were not in the POC pathway had the highest risk of readmission (odds ratio: 2.5; 95% confidence interval: 1.1–5.5).Conclusion A multidisciplinary POC pathway incorporating endocrinologist in conjunction with postdischarge weight-based fluid restriction and postoperative serum sodium levels can safely be used to reduce 30-day readmissions following ETPS.
Keywords: quality improvement; postoperative care pathway; readmissions; transsphenoidal pituitary surgery; pituitary surgery; risk factors; endocrinology; coordination of care